CARDIAC STEM CELL DENGAN INDUKSI TNFR1-BLOCKER DAN NRG-1/ERB-B4 SEBAGAI TERAPI PEREMAJAAN GAGAL JANTUNG AKIBAT PENYAKIT JANTUNG ISKEMIK - Aiman Hilmi Asaduddin; Annisa Syarifa Istighfarini; Alya Sabilah Siregar; ‘Aininna ‘Izzah Zafira; Farah Nur Adiba (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Heart Failure (HF) is a complex clinical syndrome because of cardiac abnormalities. The incidence of heart failure could reach 37.7 million in 2010. Meta-analysis research showed that stem cell can improve cardiac function. Cardiac stem cell (CSC) therapy on HF can be optimized using Tumor Necrosis Factor-? receptor type-1 (TNFR1)-Blocker and Neuregulin-1 (NRG-1)/ Erythroblastic leukemia viral oncogene homolog 4 (Erb-B4)induction. Thus, the aims of this literature review are to determine CSC potency on HF and TNFR1-Blocker and NRG-1/Erb-B4 effects on CSC therapy optimization. The method used was using medical subject headings, namely CSC, TNFR1-Blocker, NRG-1/Erb-B4, and heart failure. The inclusion and exclusion criteria have been used to eliminate inappropriate journals so there were 40 journals used for this article. The results showed that CSC could differentiate into three major cardiac lineage, cardiomyocyte, endothelial cell, and smooth muscle cell. Those components are essential for cardiac rejuvenation therapy. Besides, TNF-? have a role for contractile dysfunction and induce hypertrophy and apoptosis of cardiac myocyte. Expression level of TNFR1 was significantly increased in ischemic HF. Interaction between TNF-? and TNFR1 led to apoptosis via Receptor Interacting Protein 1 (RIP1) and inhibited CSC proliferation. Thus, TNFR1 blockade will potentially leads to apoptosis prevention and induce proliferation. In the other hand, NRG-1 proved to plays some cellular mechanism via Erb-B4. NRG-1/Erb-B4 also could increase cell mobility and inhibit apoptosis via activation of PI3K/Akt. In conclusion, signaling induction of TNFR1-blocker and NRG1/Erb-B4 have potential role to optimized CSC therapy on ischemic HF rejuvenation.